Pengaruh Pelatihan Terhadap Kinerja Karyawan Pramusaji di Breeze Lounge And Bar Royal Tulip Gunung Geulis Resort And Golf Bogor - Mentary Krisandini; Suparwi Suparwi; Darmaesti Darmaesti (Jurnal Pariwisata Indonesia, 2021)
The general purpose of writing this paper is to determine the effect of training on the performance of waitress employees at Breeze Lounge and Bar Royal Tulip Gunung Geulis Resort and Golf Bogor. This research was conducted at the Breeze Lounge and Bar Royal Tulip Gunung Geulis Resort and Golf Bogor with a qualitative descriptive research. Data collection methods used are observation, interviews, literature study and documentation. From the results of the discussion, it is known that the training at the Breeze Lounge and Bar has gone well and effectively seen from the indicators of training methods and training evaluation. Based on the recapitulation, it can be seen from the overall data, the one on one (coaching) training method is the most effective method to be implemented in the Breeze Lounge and Bar. Based on appropriate and effective training methods that can affect the speed, accuracy and personality of Breeze Lounge and Bar waiters. Apart from training, the motivation of the leader can also affect the performance of the waitresses at the Breeze Lounge and Bar Royal Tulip Gunung Geulis Resort and Golf Bogor.